Dental and Maxillofacial Manifestations of Axenfeld–Rieger Syndrome: Presentation of a Case in a 5-Year-Old Girl - Carlos-Martín Ardila; Efraín Álvarez-Martínez (Case Reports in Dentistry)
In this case study, the dental and maxillofacial manifestations of a 5-year-old girl with Axenfeld–Rieger syndrome (ARS) are described. This syndrome is characterized by craniomaxillofacial, ocular, dental, and umbilical disorders. The patient presented ocular dyscoria and corectopia, iris abnormalities, midface hypoplasia with a thin upper lip, and a protruded lower lip. Hyperplastic maxillary labial frenulum, oligodontia, ghost teeth, bilateral Class III molar and canine relationship, and right posterior crossbite were also found. An everted umbilicus with redundant periumbilical skin was evident. Early diagnosis of ARS is essential to establishing preventive and corrective measures that provide a good quality of life for patients who suffer from this syndrome.